Docker fundamentals - Neelakantan, Sreeprakash (Packt Publishing, 2018)
"Docker is a leading software container platform. Using containers, Docker guarantees that a particular application will always run the same, regardless of where it's deployed. The course begins with a basic introduction to Docker, and explore our first Hello world! example. You then move on to Docker installation and more Hello world! examples on various platforms, and explore the Docker architecture and its major components such as the Docker Registry, Docker containers, and so on. Moving ahead, you will delve deeply into understanding Docker containers, one of the most important features in Docker. We also look at container and data management, customizing Docker images using Dockerfile, uploading images to the registry, and Dockerfile best practices. Along with learning Docker, you will also learn how Docker simplifies DevOps automation. By the end of this course, you will successfully deploy applications in a Docker container."--Resource description page